Efficacy of rifaximin, a poorly absorbed rifamycin antimicrobial agent, for hepatic encephalopathy in Japanese patients. Issue 4 (9th March 2021) - Hiramine, Yasunari; Uto, Hirofumi; Mawatari, Seiichi; Kanmura, Shuji; Imamura, Yasushi; Hiwaki, Takuya; Saishoji, Akiko; Kakihara, Atsuko; Maenohara, Shigeho; Tokushige, Koichi; Ido, Akio
Abstract: Aim: Rifaximin is recommended as treatment for hepatic encephalopathy (HE) that targets intestinal bacterial flora. Although combined use with synthetic disaccharides is the standard of care worldwide, the therapeutic effects of rifaximin for overt encephalopathy (OHE) in Japanese patients have not been examined sufficiently. We examined the therapeutic effects of rifaximin for OHE in Japanese patients. Methods: A total of 76 patients who developed OHE of West Haven grade II or higher at least once within the 12 months before starting rifaximin were included. Blood ammonia levels and the incidence of OHE during the 12 months before and after starting rifaximin therapy were compared in a before‐and‐after study. Rifaximin efficacy and predictors of efficacy were also examined. Results: Post‐treatment blood ammonia levels were significantly lower than pretreatment levels. The mean annual number of OHE incidents and intravenous branched‐chain amino acid preparations used per patient were significantly lower after starting rifaximin therapy (2.51 vs. 0.76 times/year, p  < 0.001; and 71.9 vs. 20.7 preparations/year, p  = 0.003, respectively). The cumulative incidence of hospitalizations associated with HE significantly decreased after rifaximin therapy (hazard ratio 0.187; p  < 0.001). The efficacy rate, defined as the proportion of patients without OHE during the administration of rifaximin for 1 year after starting rifaximin therapy, was 65.8%. Serum albumin ≥2.7 g/dl was an independent predictor of efficacy. Conclusion: Rifaximin was associated with decreased blood ammonia levels, lower incidence of OHE, and fewer hospitalizations in Japanese patients with HE. In addition, serum albumin level was an important predictor on efficacy of rifaximin.